2015
DOI: 10.1111/jdv.13080
|View full text |Cite
|
Sign up to set email alerts
|

Rosettes and other white shiny structures in polarized dermoscopy: histological correlate and optical explanation

Abstract: Rosettes are an optical effect of crossed polarization by concentric fibrosis or horny material and hence are not lesion-specific.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 9 publications
(16 reference statements)
2
64
0
3
Order By: Relevance
“…20 Some structures such as white shiny lines or rosettes are visible only under polarized light. 21,22 Nevertheless, the choice of polarized or non-polarized light in this study only affected a few cases and did not play a major role.…”
Section: Discussionmentioning
confidence: 92%
“…20 Some structures such as white shiny lines or rosettes are visible only under polarized light. 21,22 Nevertheless, the choice of polarized or non-polarized light in this study only affected a few cases and did not play a major role.…”
Section: Discussionmentioning
confidence: 92%
“…Four dot clods were first thought to be specific for actinic keratosis and squamous cell carcinoma, and however, they are not lesion specific and are described in many neoplastic, inflammatory and infectious conditions including the following: melanoma, basal cell carcinoma, naevus, dermatofibroma, molluscum contagiosum, urticaria, cicatricial alopecia, discoid lupus erythematosus lesions and even on sun‐damaged skin. They can only be seen with polarised dermoscopes.…”
Section: Discussionmentioning
confidence: 99%
“…following: melanoma, basal cell carcinoma, naevus, dermatofibroma, 3,10-12 molluscum contagiosum, urticaria, cicatricial alopecia, discoid lupus erythematosus lesions 10,13 and even on sun-damaged skin. They can only be seen with polarised dermoscopes.…”
Section: E52mentioning
confidence: 99%
“…Many authors believe that it is due to the optical effect of polarized light. It is postulated that rosettes are formed by narrowing of infundibula or blockage by keratin [24]. Others suggested that rosettes correspond to an alternating focal hyperkeratosis and normal corneal layer and keratin-filled acrosyringeal openings.…”
Section: Discussionmentioning
confidence: 99%